Exploring the Impact of Big Data Analytics on FinTech Performance: The Mediating Role of Business Analytics Strategy in Jordanian Commercial Banks - Aldalaien, Baaeth; Al-Majali, Mohannad; Awamleh, Fawwaz Tawfiq; Al-Smadi, Raed Walid (International Journal of Economics and Financial Issues, 2025)
This research examines the impact of big data analytics (BDA) on the performance of FinTech in Jordanian commercial banks using the BAS mediating effect perspective. The analysis seeks to explore how strategic application of data analytics contributes to banking, financial technology efficiency, and innovation. 415 usable questionnaires were obtained from the staff of technical and administrative departments of different Jordanian commercial banks. The data were analyzed using Smart PLS 4, a well-known structural equation modeling software. The results showed BDA to be a positive and significant driver of FinTech performance and definitively confirmed data analytics capabilities to be significant enablers of digital banking transformation. In addition, the study finds that BAS mediates the relationship between BDA-FinTech performances partially. The partial mediation is interpreted to mean that although BDA enhances performance on its own, its effect is more pronounced with the availability of a developed analytics strategy. The paper emphasizes the importance of aligning data activities with organizational strategy in order to realize optimum value. It provides actionable implications for bank managers, policymakers, and technology leaders who are looking to harness the potential of big data to create innovative customer-focused financial solutions. By centering on the BAS role, the research also calls on institutions to commit to investing in analytics governance and strategic planning as central pillars for FinTech growth. In summary, this study adds to the existing literature on digital innovation in banking, particularly in the context of emerging economies such as Jordan.